Advances in Understanding Micro‐ and Nanoplastic Toxicity on Farmed Fish and Emerging Nutritional Interventions - Quansen Xie; Fang Chen; Xiaoping Huang; Jun Wang; Dizhi Xie (Reviews in Aquaculture, 2026)
Micro‐ and nanoplastics (MNPs), encompassing microplastics (MPs, diameters